Intersemiotic Translation Literary and Linguistic Multimodality - Pârlog, Aba-Carina.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Palgrave Pivot, 2019)
This book explores the practical aspects of intersemiotic translation, examining how different signs and sign sets can be transposed into different kinds of semiotic forms of reference. Drawing on theories from translation studies, semiotics, philosophy and stylistics, the author seeks to understand what happens when texts are translated from one genre or modality to another, and makes use of examples ranging from written texts to advertising, images, music, painting, photography, and sculpture. She also analyses related topics such as the differences between Romance and Germanic languages, the difficulties that arise when attempts are made to translate figures of speech or elements of authorial style, and how this interdisciplinary field relates to traditional language-based translation. This book will be of interest to students, teachers, translators and researchers working in the fields of translation studies and multimodality in particular. Aba-Carina Pârlog is alecturer in the Department of Modern Languages and Literatures at the West University of Timişoara, Romania. She has been teaching courses on translation studies and British literature for more than 18 years, and has also worked as a linguistic administrator for the European Personnel Selection Office in Brussels and as a translator and interpreter of English and French in Timişoara. She is the author of several books on translation and literature.
Chapter 1: Introduction -- Chapter 2: Intersemiotic Translation: Signs, Symbols and Messages -- Chapter 3: Aesthetics, Discourse and Ekphrasis -- Chapter 4: Visual and Verbal Code Translation -- Chapter 5: Direct and Indirect Intralingual Translation -- Chapter 6: The Constraints of Interlingual Translation -- Chapter 7: Conclusion.
Keywords: Translating and interpreting; Semiotics; Comparative literature; Germanic languages; Language and languages -- Style; Language Translation; Semiotics; Comparative Literature; Germanic Languages; Stylistics